2013
DOI: 10.1371/journal.pone.0083931
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and Functional Connectivity Alterations of Corticostriatal and Default Mode Network in Treatment-Naïve Patients with Obsessive-Compulsive Disorder

Abstract: BackgroundPrevious studies have demonstrated that structural deficits and functional connectivity imbalances might underlie the pathophysiology of obsessive-compulsive disorder (OCD). The purpose of the present study was to investigate gray matter deficits and abnormal resting-state networks in patients with OCD and further investigate the association between the anatomic and functional alterations and clinical symptoms.MethodsParticipants were 33 treatment-naïve OCD patients and 33 matched healthy controls. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 83 publications
(100 reference statements)
2
40
1
Order By: Relevance
“…These findings are consistent with an overactive error control system in OCD subserving suppression of prepotent responses during decision-making. Several studies of FC connectivity confirmed alteration in the fronto-striato-thalamo-cortical (i.e., [199][200][201][202][203][204][205][206][207]). The dysregulation of the fronto-striato-thalamo-cortical circuit may be one of the major findings, which can help to differentiate the two disorders, as the presence of an increased WM integrity during in pediatric and adolescent patients affected by OCD.…”
Section: Developmental Perspectivementioning
confidence: 94%
“…These findings are consistent with an overactive error control system in OCD subserving suppression of prepotent responses during decision-making. Several studies of FC connectivity confirmed alteration in the fronto-striato-thalamo-cortical (i.e., [199][200][201][202][203][204][205][206][207]). The dysregulation of the fronto-striato-thalamo-cortical circuit may be one of the major findings, which can help to differentiate the two disorders, as the presence of an increased WM integrity during in pediatric and adolescent patients affected by OCD.…”
Section: Developmental Perspectivementioning
confidence: 94%
“…Within nodes of the SN, volumetric changes have been identified in the ACC, striatum and thalamus (Gilbert et al, 2008; Hoexter et al, 2012; Hou et al, 2013; Atmaca et al, 2016). Functionally, the ACC appears to be abnormally altered during disease-relevant tasks.…”
Section: Abnormalities Of Sn-cstc Loop Circuits In Psychiatric Illnessesmentioning
confidence: 99%
“…Although these inconsistencies might be due to the clinical characteristics of each dataset 25,26 , other studies suggested that the fronto-striatal circuit is not the only target should be considered. In other words, studies have suggested that there were abnormalities in addition to those observed in the fronto-striatal circuit, including the frontoparietal and default mode networks 5,27,28 . No study has quantitatively evaluated the relative importance of the fronto-striatal circuit relative to the whole brain.…”
mentioning
confidence: 99%